HUBUNGAN ANTARA WAKTU TUNGGU PELAYANAN RESEP RACIKAN TERHADAP KEPUASAN PASIEN DI APOTEK MEDIRA FARMA KOTA BENGKULU BULAN APRIL TAHUN 2021 - Yustisia, Nova; Versita, Riana; Yolanda, Sefty; Dominica, Dwi (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
Pharmaceutical is a direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving good results that are sure to improve the quality of life of patients. One of the quality of pharmacy services is waiting time. The purpose of this study was to see the relationship between waiting time for concoction prescription services and patient satisfaction at the Medira Farma Pharmacy, Bengkulu City in April 2021. This study used observational analytic method with astudy approach cross sectional. The research instrument is an observation sheet, the sample of this research is 30 respondents. The sample was determined using purposive sampling technique. Data analysis was carried out using the chi square statistical test.. The results of the study showed that the level of patient satisfaction at the Medira Farma Pharmacy was 86.67% satisfied and 13.33% dissatisfied, while the waiting time for concoction prescription services at Medira Farma Pharmacy was said to be in accordance with the standard of 73.33% and not according to the standard of 26 ,67%. In thestatistical test chi square , the p value = 0.257 with the value = 0.05. The results of the data can be concluded that there is no relationship between waiting time for concoction prescription services to patient satisfaction at the Medira Farma Pharmacy, Bengkulu City with a closeness level of 0.23 which means low. The advice given is that Medira Farma Pharmacy should provide comfortable and adequate waiting room facilities to avoid patients feeling bored.